Inflammatory bowel diseases, chronic liver diseases and the lung. Issue 2 (21st January 2016) - Rodriguez-Roisin, Roberto; Bartolome, Sonja D.; Huchon, Gérard; Krowka, Michael J.
This review is devoted to the distinct associations of inflammatory bowel diseases (IBD) and chronic liver disorders with chronic airway diseases, namely chronic obstructive pulmonary disease and bronchial asthma, and other chronic respiratory disorders in the adult population. While there is strong evidence for the association of chronic airway diseases with IBD, the data are much weaker for the interplay between lung and liver multimorbidities. The association of IBD, encompassing Crohn's disease and ulcerative colitis, with pulmonary disorders is underlined by their heterogeneous respiratory manifestations and impact on chronic airway diseases. The potential relationship between the two most prevalent liver-induced pulmonary vascular entities, i.e. portopulmonary hypertension and hepatopulmonary syndrome, and also between liver disease and other chronic respiratory diseases is also approached. Abnormal lung function tests in liver diseases are described and the role of increased serum bilirubin levels on chronic respiratory problems are considered. Lung–gut cross-talk: the association of IBD with respiratory multimorbitidies, including COPD and bronchial asthma http://ow.ly/UT94a